2015
DOI: 10.11622/smedj.2015189
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of albuminuria among diabetic patients in a primary care setting in Singapore

Abstract: INTRODUCTIONMicroalbuminuria is an early sign of kidney damage. The prevalence of microalbuminuria in Singapore has been reported to be 36.0%-48.5%. However, the prevalence of microalbuminuria reported in these studies was determined with one urine sample using a qualitative urine test. The aim of this study was to determine the prevalence of micro-and macroalbuminuria using a more stringent criterion of two positive quantitative urine albumin-creatinine ratio (ACR) tests. METHODSWe conducted a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
(19 reference statements)
2
13
1
Order By: Relevance
“…The prevalence of MAU increased to 74% in the presence of more than 3 comorbidities [31][32][33]. The present study confirms previous trials that have demonstrated a strong relationship between MAU and the level of systolic BP [5,6]. Most of our RH patients had severe, second and third degree hypertension, with high CV risk.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The prevalence of MAU increased to 74% in the presence of more than 3 comorbidities [31][32][33]. The present study confirms previous trials that have demonstrated a strong relationship between MAU and the level of systolic BP [5,6]. Most of our RH patients had severe, second and third degree hypertension, with high CV risk.…”
Section: Resultssupporting
confidence: 88%
“…It was demonstrated that MAU is a marker of endothelial dysfunction that predicts a greater incidence of target organ damage, cardio-and cerebrovascular events and that its reduction lowers these comorbidities [5]. The reported prevalence of MAU is highly variable among studied populations, ranging from 7% to 58.4% [6,7]. This variation can be explained by differences in population characteristics, investigation methods and prescribed drugs [8 -10].…”
mentioning
confidence: 99%
“…No significant association was found between two groups regarding TC, TG, HDL and LDL. A study conducted in china also found similar result [50].…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, the population who might potentially benefit from nephropathy monitoring is quite small; among Asian people with diabetes mellitus, only 0.9% had albuminuria and normal blood pressure. 24 This small fraction of the population may have made it difficult to detect any positive effect of nephropathy monitoring on subsequent change in outcomes, even in our analysis restricted to normotensive individuals with diabetes mellitus. Another possible explanation for our findings is that intensive control of diabetes mellitus and hypertension is still difficult, even when physicians detect signs of renal function impairment, because intensive glycemic and blood pressure control require the patient's recognition of the disease and implementation of lifestyle changes.…”
Section: Discussionmentioning
confidence: 93%